Pemetaan Hasil Panen Padi di Jawa Tengah menggunakan Metode Poligon Thiessen - Erni Erni; Adi Nugroho (Journal of Information System Research (JOSH), 2022)
Rice is the staple food of Indonesian people. Processed rice comes from the rice plant. Along with the increasing population in Central Java, the need for rice is increasing from year to year. Data mapping is needed to overcome the reduction in the quantity of rice yields. Rice yields in Central Java have increased and decreased which are influenced by rainfall each year, namely in 2019-2020. The planting area that produces the most harvest is Grobogan, while the least production is Surakarta. Due to the very high rainfall that affects crop yields in Surakarta, rice plants experience flooding and damage rice yields.